37. SERVICE READINESS FOR HYPERTENSION AND DIABETES MANAGEMENT IN PRIMARY CARE FACILITIES OF THUA THIEN HUE PROVINCE: AN ANALYSIS OF WHO-SARA DATA IN 2018 AND 2024 (Vietnam Journal of Community Medicine, 2025)
Hue city Department of Health
Keywords: Service readiness; non-communicable diseases; primary care; healthcare disparities